Gambaran pengetahuan pemeliharaan kesehatan jaringan periodontal pada usia remaja - Fauziah, Salsa; Sundjojo, Mikha (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Periodontal disease is one of oral health problems. Periodontal tissue health can be affected by hormonal conditions, age, and systemic diseases. Maintaining oral health is a key strategy for enhancing overall well-being, and understanding periodontal tissue health is crucial—particularly during adolescence, a developmental phase characterized by hormonal fluctuations and continuous physical growth.. Method: This research is a descriptive observational study with a cross sectional design. The data were collected using a questionnaire instrument containing knowledge-based questions about oral health and periodontal tissues distributed to 110 students aged 15-17 years at Citra Islamic High School. Results: This study illustrates that among 110 students, 10 students (9%) have a good level of knowledge, 41 students (37%) are categorised as sufficient, 60 students (54%) have a poor level of knowledge. Conclusion: The level of knowledge about maintaining periodontal dental and oral health at the age of 15-17 years of most Citra Islamic High School students is still in the poor category, so dental and oral health education is needed to increase knowledge about oral health.